2017
DOI: 10.1016/j.nlm.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Brain correlates of memory reconsolidation: A role for the TPJ

Abstract: In this paper, we investigate the process by which new experiences reactivate and potentially update old memories. Such memory reconsolidation appears dependent on the extent to which current experience deviates from what is predicted by the reactivated memory (i.e. prediction error). If prediction error is low, the reactivated memory is likely to be updated with new information. If it is high, however, a new, separate, memory is more likely to be formed. The temporal parietal junction TPJ has been shown acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…It should be noted that in several of the prior studies reporting reminder-potentiated reconsolidation interference, such effects were expressed not in forgetting of studied materials, but in intrusion effectsessentially source memory failures, in which items from distractor lists are reported as belonging to target lists (Hupbach et al, 2007;Hupbach, Hardt, Gomez, & Nadel, 2008;Hupbach, Gomez, & Nadel, 2009;Simon, Gómez, Nadel, & Scalf, 2017;Wichert et al, 2013). Hupbach and colleagues have argued that such intrusions do not only reflect source memory failures, since they were generally unidirectional (i.e., later objects were reported as part of the activated-interfered list, but not vice versa; Hupbach et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that in several of the prior studies reporting reminder-potentiated reconsolidation interference, such effects were expressed not in forgetting of studied materials, but in intrusion effectsessentially source memory failures, in which items from distractor lists are reported as belonging to target lists (Hupbach et al, 2007;Hupbach, Hardt, Gomez, & Nadel, 2008;Hupbach, Gomez, & Nadel, 2009;Simon, Gómez, Nadel, & Scalf, 2017;Wichert et al, 2013). Hupbach and colleagues have argued that such intrusions do not only reflect source memory failures, since they were generally unidirectional (i.e., later objects were reported as part of the activated-interfered list, but not vice versa; Hupbach et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the interaction between perceived gaze direction and social decision making may also be influenced by the level of empathy in participants which we unfortunately did not measure. Second, studies have shown that TPJ is sensitive to prediction error, which means the degree to which current information is inconsistent with expectation, in various domains including social interaction (Behrens et al, 2008 ; Simon et al, 2017 ). People in multiple-rounds social interactions may employ TPJ to guide behaviors based on previous experiences.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that in several of the prior studies reporting reminder-potentiated reconsolidation interference, such effects were expressed not in forgetting of studied materials, but in intrusion effects – essentially source memory failures, in which items from distractor lists are reported as belonging to target lists ( Hupbach et al, 2007 , Hupbach et al, 2008 Hupbach et al, 2009 , Simon et al, 2017 , Wichert et al, 2013 ). Hupbach and colleagues have argued that such intrusions do not only reflect source memory failures, since they were generally unidirectional (i.e., later objects were reported as part of the activated-interfered list, but not vice versa; Hupbach et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%